Group B Streptococcus Screening in Antenatal Patients in A Tertiary Care Center in Lahore - Maroofa Habib, Tayyaba Majeed, Mariam Malik (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Group B Streptococcus (GBS) is a significant contributor to the infectious morbidity of both mothers and newborns and is one of the most important pathogens associated with early onset neonatal sepsis around the world. It is important to recognise that the maternal genital tract is a source of vertical transmission during delivery. Although the use of antenatal screening and intrapartum antibiotic prophylaxis (IAP) to prevent neonatal infection has been recommended, there is limited evidence from LMICs. Objective: To understand the prevalence of maternal GBS colonization and effectiveness of intrapartum antibiotic prophylaxis (IAP) to prevent maternal and neonatal infectious complications. Materials & Methods: A prospective cohort study was carried out at a tertiary care teaching hospital in the period between 1st January, 2022 and 1st June, 2024, which was STROBE compliant.Methods: This was a STROBE-compliant prospective cohort study carried out at a tertiary care teaching hospital from 1st January, 2022 to 1st June, 2024. Combined lower vaginal and rectal screening for GBS colonization was performed on 350 pregnant women at 35-37 weeks of gestation by standard microbiological culture. Women with GBS infection were administered IAP according to guidelines.Guideline-based IAP was administered to GBS positive women. Maternal outcomes included intrapartum fever, chorioamnionitis, postpartum endometritis, and puerperal sepsis and neonatal outcomes included early onset neonatal sepsis, respiratory distress syndrome, admission to NICU, low Apgar score, neonatal pneumonia, and mortality. Multiple logistic regression was used to determine the predictors of neonatal sepsis. Results: The prevalence of maternal GBS colonization was 18.0% (63 participants). Every aspect of the pregnancy was significantly more common in colonized mothers, including prolonged rupture of membrane and UTI in pregnancy. IAP was associated with significantly reduced incidence of EONS (1.8% vs 28.6%, p<0.001), NICU admissions (8.9% vs 42.9%, p=0.006), RDS and neonatal pneumonia. Maternal GBS colonization (adjusted odds ratio [AOR]=3.12, p=0.003) and prolonged rupture of membranes (AOR=2.01, p=0.021) were independent risk factors for neonatal sepsis, while adequate intrapartum prophylaxis was protective (AOR=0.42, p=0.018) in logistic regression analysis. Conclusion: GBS screening plus intrapartum antibiotic prophylaxis is highly effective in preventing infectious morbidity in the neonatal period, and should be encouraged as routine obstetric practice, especially in areas with a high incidence of neonatal sepsis. Keywords: Group B Streptococcus, maternal colonization, neonatal sepsis, intrapartum antibiotic prophylaxis, NICU admission, maternal infection.